A rich and diverse fauna: an illustrated guide to the cetoniines of Ghana with comparisons to Ivory Coast and Benin (Coleoptera: Scarabaeidae: Cetoniinae) - Philips, T. Keith; Mudge, Alan D.; Orozco, Jesus; Neidlinger, Robert; Beinhundner, Gerhard; Joly, Claude (Zootaxa, 2022)
The currently known cetoniine fauna of Ghana is discussed and illustrated. It now includes 60 genera and 148 taxa, including 9 subspecies. Comparison to the adjacent countries of Ivory Coast and nearby Benin gives evidence that the faunas of all three countries surprisingly may still be grossly under-sampled and hence poorly known for what is considered a relatively well-known group of beetles. At least 22 species known from both Ivory Coast and Benin are expected to be found in Ghana but still have yet to be reported. Notes on several species concepts and the alternate use of names are also given to clarify the taxonomy of the taxa known from this area.